Prevalence of obesity among adults in Ras Al Khaimah, United Arab Emirates - Kalavathy, Ramasamy; Al Araj, Sumaya Ahmed; Rabbani, Syed Arman (International Journal of Research in Medical Sciences, 2019)
Background: There is an increasing prevalence of obesity globally which is associated with Non Communicable Diseases. As this trend continues even in UAE we decided to focus on determining the prevalence of obesity among adults in Ras Al Khaimah (RAK), UAE. Methods: This was a retrospective observational study done in adults between the age group of 18 to 77 years using convenience sampling technique in 544 subjects. Anthropometric, bio chemical, clinical and demographic data was collected by direct interview for four consecutive years, i.e. from 2013 to 2016. Body Mass Index (BMI) was analyzed to classify individuals as overweight (BMI 25.0-29.9kg/m²), Obese grade I (BMI 30.0-34.9kg/m²), Obese grade II (BMI 35.0-39.9kg/m²) and obese grade III (BMI > 40.0kg/m²). Results: Data was obtained from 544 subjects and considered for analysis. Our results showed that the mean age of the study population was 39.29±13.43 years, the mean weight was 75.35±15.65 kilograms and the mean BMI was 27.62±5.43kg/m2. A total of 67.6% of the study population was either overweight or obese. The prevalence of overweight is 36.2% followed by obesity prevalence of 31.4% of which 22.8% were categorized as Grade I obese, 5.5% Grade II obese and 3.1% Grade III obese. We found that higher proportions of males were in overweight and obese category compared to females. Conclusions: The results derived from our study shows that obesity and overweight are widespread among Ras al khaimah population with the obesity prevalence of 31.4%. Hence, policy makers should focus on preparing national nutritional strategies and implement protocols to overcome this burden by giving practical solutions.